Inverted ILM Flap for the Treatment of Myopic Macular Holes: Healing Processes and Morphological Changes in Comparison with Complete ILM Removal - Maurizio Mete; Alessandro Alfano; Emilia Maggio; Massimo Guerriero; Grazia Pertile (Journal of Ophthalmology)
Purpose. To investigate the microstructural changes after successful myopic macular hole (MMH) surgery, comparing inverted ILM flap and complete ILM removal techniques, and their association with visual function. Methods. Spectral-domain optical coherence tomography (SD-OCT) was used to evaluate both external limiting membrane (ELM) and ellipsoid zone (EZ) recovery in 40 eyes of 39 patients who underwent pars plana vitrectomy with either inverted internal limiting membrane flap technique (n=27) or complete ILM removal (n=13) to achieve MH closure. The association between ELM and EZ recovery and visual acuity was also investigated. The patients were followed up at 1 year. Results. ELM and EZ was recovered in 72% and 62% of cases, respectively, regardless of the surgical techniques 1 year after surgery. A strong positive association between the ELM and EZ recovery and the mean BCVA was found: regardless of the surgical technique, this was statistically significant at each time point (p<0.05). None of the baseline variables were found to act as predictive factors for either ELM or EZ. Conclusion. The inverted ILM flap technique did not affect the MMH healing processes compared to complete ILM removal. Thus, the presence of the ILM plug did not interfere with the restoration of both ELM and EZ, which correlated with functional recovery.